2019
DOI: 10.1002/anie.201812697
|View full text |Cite
|
Sign up to set email alerts
|

Ion Mobility Mass Spectrometry Measures the Conformational Landscape of p27 and its Domains and how this is Modulated upon Interaction with Cdk2/cyclin A

Abstract: Intrinsically disordered proteins have been reported to undergo 'disorder to order' transitions upon binding to their partners in the cell. The extent of the ordering on binding and the lack of order prior to binding is difficult to visualize with classical structure determination methods. Binding of p27 to the Cdk2/cyclin A complex is accompanied by partial folding of p27 in the KID domain, with the retention of dynamic behaviour for function, particularly in the C-terminal half of the protein, positioning it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…It was found that the KID domain of p27 (p27 KID ), which folds upon binding to Cdk2/cyclin A, causes the rigid dimer to become more dynamic. As expected, full-length p27 (p27 FL ) is tamed upon binding, with the most extended conformations no longer being accessible upon complex formation ( Beveridge et al, 2019b ). In this work, the strength of IMMS is its ability to visualize both the bound and unbound form of an IDP, without the preference for the bound form that is displayed by many techniques.…”
Section: Native Mass Spectrometrymentioning
confidence: 56%
“…It was found that the KID domain of p27 (p27 KID ), which folds upon binding to Cdk2/cyclin A, causes the rigid dimer to become more dynamic. As expected, full-length p27 (p27 FL ) is tamed upon binding, with the most extended conformations no longer being accessible upon complex formation ( Beveridge et al, 2019b ). In this work, the strength of IMMS is its ability to visualize both the bound and unbound form of an IDP, without the preference for the bound form that is displayed by many techniques.…”
Section: Native Mass Spectrometrymentioning
confidence: 56%
“…Because of this, as has been shown from our research, so far, the D SD parameter accounts for the multidimensional molecular conformation and electronic structure of the analyte ion. We may add that even with the employment of some of the most prominent MS methods, for instance, the ion mobility mass spectrometry, where the method operates within the spans of the measurement times between minutes and μs to ms, the MS structural information is mainly limited to 2D analysis as has been shown from the accumulated research more recently (Fuller et al, 2018;Beveridge et al, 2019;Chen et al, 2019;Woodall et al, 2019). The methodological efforts consisting of the computation of collision cross section (CCS) yields, in fact, to energetics of analyte ions, presumably corresponding to a 3D molecular conformation, which is con-nected with the drift time and the velocity of the MS ions via the Mason-Schamp equation.…”
Section: Discussionmentioning
confidence: 99%
“…A number of groups are now using ion mobility spectrometry-mass spectrometry (IMS-MS) to study biomolecular structure and dynamics. In IMS, the unique ion mobilities are determined by measuring the time required to traverse a drift tube filled with an inert buffer gas. The mobility measurements can be related to the ions’ orientationally averaged collision cross section, which effectively reports on an ion’s shape .…”
Section: Introductionmentioning
confidence: 99%